PERSEFEKTIF IN HUMAN TRAFFICKING CRIME LAW NUMBER 39 OF 1999 ON HUMAN RIGHTS CASE AGAINST CHILD TRAFFICKING IN MEDAN - Putu Ayu Dewi, Ida Monika (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2020)
Laws are the norms that govern all human actions that can be done and should not be carried out both written and unwritten and have sanctions, so that the entry into force of these rules can be forced or coercive and binding for all the people of Indonesia. The most obvious form of manifestation of legal sanctions appear in criminal law. In criminal law there are various forms of crimes and violations, one of the crimes listed in the criminal law, namely the crime of Human Trafficking is often perpetrated against women and children. Human Trafficking is any act of trafficking offenders that contains one or more acts, the recruitment, transportation between regions and countries, alienation, departure, reception. With the threat of the use of verbal and physical abuse, abduction, fraud, deception, abuse of a position of vulnerability, example when a person has no other choice, isolated, drug dependence, forest traps, and others, giving or receiving of payments or benefits women and children used for the purpose of prostitution and sexual exploitation. These crimes often involving women and children into slavery.Trafficking in persons is a modern form of human slavery and is one of the worst forms of violation of human dignity (Public Company Act No. 21 of 2007, on the Eradication of Trafficking in Persons). Crime human trafficking crime has been agreed by the international community as a form of human rights violation.